Droplet Size Reduction of Self-Emulsifying Drug Delivery System (SEDDS) Using the Hybrid of Medium and Long-Chain Triglycerides - Kaijie Qian; Yuanyuan Lin; Bingxiang Zhao; Xiangrui Liu (Pharmaceutics)
Background: Self-emulsifying drug delivery system (SEDDS) is widely used to improve the oral bioavailability of hydrophobic drugs. Emulsion droplet size was revealed to be a critical parameter that influences the thermodynamic stability, drug solubility, and drug absorption of the SEDDS. A high proportion of surfactant and/or co-surfactant was usually employed to reduce the particle size, which may lead the low drug loading and undesirable gastrointestinal toxicity. Methods: This manuscript proposed a novel strategy to reduce the particle size of emulsions using the hybrid of medium and long-chain triglyceride (MCT and LCT) SEDDS without promoting the concentration of surfactants and co-surfactants. The composition of SEDDS was selected based on the drug solubility. Particle size distribution and zeta potential of emulsion particles were determined using the dynamic light scattering technique. The bioavailability of formulations was evaluated in a mouse model. Results: The particle size of the emulsion was reduced from 113.50 ± 0.34 nm (MCT SEDDS) and 371.60 ± 6.90 nm (LCT SEDDS) to 21.23 ± 0.30 nm (MCT&LCT SEDDS). Progesterone, a poorly water-soluble drug, was selected as the model drug in the investigation of SEDDS. The hybrid of MCT&LCT progesterone SEDDS exhibited reduced particle size, enlarged self-emulsifying ranges, and increased drug content in the aqueous phase after lipolysis compared with the conventional mono-MCT or LCT SEDDS. In addition, the bioavailability of progesterone in the MCT&LCT SEDDS formulation was 3.82-fold higher than that of Utrogestan® (a clinical oral administrated product) in a mouse model.